Computer Aided System To Improve Vocabulary Learning At SMAN 2 Gowa - Aswad, Devita Hajaratul; Firman; Junaid (FKIP Unismuh Makassar, 2025)
This research aimed to know the vocabulary improvement students when use the Computer Aided System at class X II SMA Negeri 2 GOWA . This research utilized a pre-experimental research method with a quantitative approach which involved 38 samples of the students in the class X at SMA Negeri 2 GOWA. The results of the research show that there is an increase in students' vocabulary after getting to know and using the computer aided system. This proves that the average post test score is more significant than the pre test (81.8>54.7). From the t-test findings, the t-test value is superior to the t-table (29.4>2.026) at a significance level of 0.05 with degrees of freedom (df) = 37, which means there is a significant difference regarding students' vocabulary. before and after implementing the Computer Aided System. it is also said that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. The research results are effective in increasing students' vocabulary.